Prevalence and intensity of persistent post-surgical pain following breast cancer surgery: a systematic review and meta-analysis of observational studies. (September 2020) - Wang, Li; Cohen, Jared C.; Devasenapathy, Niveditha; Hong, Brian Y.; Kheyson, Sasha; Lu, Daniel; Oparin, Yvgeniy; Kennedy, Sean A.; Romerosa, Beatriz; Arora, Nikita; Kwon, Henry Y.; Jackson, Kate; et al.
Abstract: Background: The prevalence and intensity of persistent post-surgical pain (PPSP) after breast cancer surgery are uncertain. We conducted a systematic review and meta-analysis to further elucidate this issue. Methods: We searched MEDLINE, Embase, CINAHL, and PsycINFO, from inception to November 2018, for observational studies reporting persistent pain (≥3 months) after breast cancer surgery. We used random-effects meta-analysis and the Grading of Recommendations, Assessment, Development and Evaluations approach to rate quality of evidence. Results: We included 187 observational studies with 297 612 breast cancer patients. The prevalence of PPSP ranged from 2% to 78%, median 37% (inter-quartile range: 22–48%); the pooled prevalence was 35% (95% confidence interval [CI]: 32–39%). The pooled pain intensity was 3.9 cm on a 10 cm visual analogue scale (95% CI: 3.6–4.2 cm). Moderate-quality evidence supported the subgroup effects of PPSP prevalence for localized pain vs any pain (29% vs 44%), moderate or greater vs any pain (26% vs 44%), clinician-assessed vs patient-reported pain (23% vs 36%), and whether patients underwent sentinel lymph node biopsy vs axillary lymph node dissection (26% vs 43%). The adjusted analysis found that the prevalence of patient-reported PPSP (any severity/location) was 46% (95% CI: 36–56%), and the prevalence of patient-reported moderate-to-severe PPSP at any location was 27% (95% CI: 10–43%). Conclusions: Moderate-quality evidence suggests that almost half of all women undergoing breast cancer surgery develop persistent post-surgical pain, and about one in four develop moderate-to-severe persistent post-surgical pain; the higher prevalence was associated with axillary lymph node dissection. Future studies should explore whether nerve sparing for axillary procedures reduces persistent post-surgical pain after breast cancer surgery.